Optimasi Dynamic Economic Dispatch pada Sistem Tenaga Hibrida Berbasis Photovoltaic Menggunakan Algoritma Turbulent Flow of Water-Based Optimization - Moh. Erdianto Triputradi; Aryani , Ni Ketut; Wibowo, Rony Seto; Oktaviani , Berliandra; Najmy, Achsan (Jurnal Serambi Engineering, 2025)
The Increasing of living population, which impacts the increasing need for loads, is a challenge for plants in providing the need for electrical loads. The depletion of supplies and the high price of fossils constrain the cost of generating thermal plants. Therefore, a combination of alternative Photovoltaic (PV) energy power generation is needed to reduce the cost of generating thermal plants. Dynamic Economic Dispatch (DED) is one of the optimization techniques in power plants to determine the combination of output power in each generator in each period. This paper proposes an optimization technique to solve the DED problem in a hybrid PV base power system using Turbulent Flow Water-Based Optimization (TFWO) Method. This paper will compare the results and analysis of total generation costs before and after using PV plants. The total generation cost shows that the generation cost using PV can reduce the generation cost by $302,799.67.